THE EFFECTIVENESS OF SEMANTIC MAPPING AS PREWRITING ACTIVITY IN ARGUMENTATIVE WRITING - Ance Jusmaya; Afriana Afriana (Universitas Putera Batam, 2019)
At present, the ability to write scientifically becomes an important skill mastered by students. Students need to have good writing skills using reasoning and logic that focuses on what must be believed or done based on mechanisms, such as doing conceptual analysis and arguments for problem solving and decision making. The concept of semantic mapping is an effective strategy to improve student writing skills. This study explores the effectiveness of the concept of semantic mapping in the development of students' writing skills in essay writing. This study was classified into a quasi-experimental design. In this study the population is students of Universal Batam University who are registered in the 2018-2019 academic year. The instrument of this research is a writing test. Data were analyzed with several analyzes, namely normality testing, homogeneity testing, and hypothesis testing. In testing the research hypothesis, the researcher used the t-test for the related sample and the Wilcoxon test. Based on the analysis it was found that the average score of students in the pre test was 7.89 and the average score of the students in the post test was 12. T-score count is t = 3.83 and a significant standard of 0.05. While t table is only 2,306. Because t count is greater than t table (tobserved> t table), so the null hypothesis (Ho) is rejected and the alternative hypothesis (Hi) is accepted. So, based on these results, it was concluded that there was a statistical difference between the pre-test at the 0.05 level. This means that learning argumentative writing based on the theory of semantic mapping has a significant influence on students' argumentative writing skills.